Espelho submerso: bi-filme entre a literatura e o audiovisual - Mariano Filho, Domingos Sávio (2024)
This research aims to investigate experimental processes of creation in contemporary arts in accordance with the Concentration Area Poetics of creation and thought in Arts, Research Line 2: Art and Creation Process: Contemporary poetics, of the Postgraduate Program in Arts, ICA, UFC. The main objective seeks to reflect on the development of a transmedia work entitled Espelho Submerso (2024), between literature and audiovisual, adopting bi-film as a methodological and creative procedure and the conceptual propositions of image-hole and word-hole, coined by Marguerite Duras (1914-1996). In this process, the strategies developed and theorized by the French writer and filmmaker from the 1960s onwards in the interview given to Xavier Gautier (Les parleuses, 1975) were taken up, and whose elements were expanded in the film essay Les Mains négatives (1978), in the novel Le Ravissement de Lol V. Stein (1964), in the novel The Lover (1984) and in the essay Écrire (1993). In light of its methodological and aesthetic-critical propositions, we produced a bi-film experimenting, in parallel, with the creation of the literary text and the audiovisual editing. The creative process operated as an open work based on photographic, literary, oral and filmic experiments, producing aesthetic dialogues between the processes of creation and the field of the hole-event (traumatic subjective experiences), linked to the hole-image and to the word-hole. We sought to contribute to the expansion of the aesthetic discussion on Durassian methodologies between 1960 and 1990, delving deeper into the concept of event-hole understood as the engine of artistic creation. We hope to expand the powerful dialogues raised between audiovisual studies, philosophy, psychoanalysis and literature.